The drug likeness analysis of anti-inflammatory clerodane diterpenoids - Zheling Feng; Jun Cao; Qingwen Zhang; Ligen Lin (BMC, 2020)
Abstract Inflammation is an active defense response of the body against external stimuli. Long term low-grade inflammation has been considered as a deteriorated factor for aging, cancer, neurodegeneration and metabolic disorders. The clinically used glucocorticoids and non-steroidal anti-inflammatory drugs are not suitable for chronic inflammation. Therefore, it's urgent to discover and develop new effective and safe drugs to attenuate inflammation. Clerodane diterpenoids, a class of bicyclic diterpenoids, are widely distributed in plants of the Labiatae, Euphorbiaceae and Verbenaceae families, as well as fungi, bacteria, and marine sponges. Dozens of anti-inflammatory clerodane diterpenoids have been identified on different assays, both in vitro and in vivo. In the current review, the up-to-date research progresses of anti-inflammatory clerodane diterpenoids were summarized, and their druglikeness was analyzed, which provided the possibility for further development of anti-inflammatory drugs.